Congenital Syphilis: A Case Report - Saujan Subedi; Jayanti Jwarchan; Shashwata Raj Pandit; Saraswoti Neupane (Nepal Journal of Dermatology, Venereology & Leprology)
Congenital syphilis is a chronic infectious disease caused by Treponema pallidum, a spirochete acquired in-utero by the fetus. Syphilis continues to affect pregnant population, in spite of various measures to control. Here we report a case of congenital syphilis in a two-year-old male child.